Evaluation of a commercial multispecies rapid test for anti-Leishmania infantum antibodies in unconventional animal species - Sergio Villanueva-Saz; Ana González; María D. Pérez; Delia Lacasta; Antonio Fernández; Pablo Quilez; Aurora Ortín; David Guallar; Álex Gómez; Diana Marteles-Aragüés (Veterinary Research Communications, 2026)
Leishmania infantum is a vector-borne protozoan causing zoonotic visceral leishmaniasis in the Mediterranean basin, where dogs are the primary reservoir. However, infection in various domestic and wild mammals raises questions about their epidemiological roles. Reliable diagnosis in non-canine species remains challenging, as most serological assays are developed for dogs and cats. This study evaluated a commercially available multispecies rapid immunochromatographic test (Uranotest ® Leishmania feline) for detecting anti- Leishmania antibodies in a diverse panel of domestic and non-domestic animals. A total of 186 serum samples from different species were analyzed, previously classified as seropositive ( n = 65) or seronegative ( n = 121) using an in-house ELISA as reference. Immunochromatographic rapid test performance was compared to ELISA results using Cohen’s kappa to assess agreement. Overall agreement reached 82.3% (κ = 0.56), indicating moderate concordance. This immunochromatographic test correctly identified all positive and negative canine and feline samples and showed perfect agreement in other carnivores such as mink and wolves. In contrast, all herbivorous species, including alpaca, horses, goats, llama, sheep, bison, and dromedaries, produced negative results by the rapid test despite ELISA seropositivity, suggesting limited affinity of the conjugate for herbivore immunoglobulins. These findings indicate that, while the assayed rapid test is suitable for detecting anti- Leishmania antibodies in non-herbivorous species, it is unreliable for herbivores. The study highlights the importance of species-specific validation of serological assays and suggests that rapid tests using protein A conjugates may have restricted cross-species utility, reinforcing the need for adapted diagnostic tools in multispecies and wildlife contexts.